Research on the Distributed Propeller Slipstream Effect of UAV Wing Based on the Actuator Disk Method - Mingzhi Cao; Kun Liu; Chunqiang Wang; Jingbo Wei; Zijie Qin (Drones, 2023)
Distributed electric propulsion technology has great potential and advantages in the development of drones. In this paper, to study the slipstream effect of distributed propellers, the actuator disk method was used to verify a single propeller, and the calculated thrust was in good agreement with the test results. Then, based on the actuator disk method, the influence of different installation positions on the slipstream effect was studied, and the distributed propeller layout was optimized by a genetic algorithm to improve the low-speed performance of the unmanned aerial vehicle (UAV) during the take-off phase and increase the cruise duration. The analysis results showed that the lift of the wing will be larger when the propellers are higher than the wing. The wing lift and drag of the counter-rotating are less than those of the co-rotating. Compared with the original layout, the lift coefficient of the optimized distributed propeller layout is significantly increased by 30.97%, while the lift/drag ratio is increased by 7.34%. Finally, we designed the test platform and qualitatively verified the calculated results without quantitative verification.